2023
DOI: 10.1021/acs.macromol.3c00086
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Polar Functionalized Polyolefins with High Biomass Content

Abstract: Introducing polar biomass groups into polyolefins can not only improve their nonpolar nature but also conform to the concept of sustainable development. Now, an efficient route to generate polar functionalized polyolefins with high biomass content is reported. Two kinds of bioresourced comonomers are designed by assembling biomass groups (oleyl and cinnamyl groups) with the norbornene structure and inserted into the polyolefins by phosphine-sulfonate palladium-catalyzed copolymerization reactions. The norborne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Introducing comonomers into polyethylene deeply affects their thermal properties. 37 Usually, the melting point (T m ) of the linear polyethylene is higher than 120 °C. [38][39][40] Comparably, the T m (86.1-97.3 °C) of the resulting copolymers decreased after inserting mono-NBFn (Table 1, entries 1-5).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Introducing comonomers into polyethylene deeply affects their thermal properties. 37 Usually, the melting point (T m ) of the linear polyethylene is higher than 120 °C. [38][39][40] Comparably, the T m (86.1-97.3 °C) of the resulting copolymers decreased after inserting mono-NBFn (Table 1, entries 1-5).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The incorporation of polar comonomers is expected to modify the surface properties of polyolefin materials. 17 The surface properties of the copolymer were studied by water contact angle (WCA) test (Figure 4, Table 2, entries 1-8, entries 11-14, with a dosage of 0.3%-1.9%, Figure 5, entries 1-9). In general, the higher the content of polar monomers in copolymers, the lower the WCA.…”
Section: Surface Properties Of Copolymersmentioning
confidence: 99%
“…15 Therefore, the low hydrophilicity and high tolerance to polar groups of transition metal catalysts make them highly attractive candidate catalysts. [16][17][18][19] More importantly, nickel catalysts with lower prices and higher soil content have developed rapidly in the field of nickel catalyzed olefin polymerization compared to precious metal palladium catalysts. [20][21][22][23][24][25] Especially in recent years, neutral phosphorus phenol nickel catalysts with excellent polar monomer copolymerization performance have flourished.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to enchain MCP units in a controlled fashion that reduces the 4MP crystallinity, allowing a better tuning of mechanical and physical properties, without strongly affecting the glass transition temperature and transparency. Indeed, we selected this comonomeric unit since the corresponding poly­(methylene-1,3-cyclopentane) homopolymer (PMCP) has a T g of about 20 °C, similar to that of iP4MP, and also because the introduction of a cyclic group can improve the optical properties of polyolefin materials in the visible region of the electromagnetic spectrum. Thus, this strategy allows obtaining thermoplastic materials that retain the unique properties of iP4MP but are characterized by improved toughness and deformability. Both the roles of amorphous and crystalline phases have been analyzed in detail to study the ductile behavior observed below the glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%